Intubating conditions, onset, duration and side effects with rocuronium and atracurium: A comparative - Rashmi Naik; Rashmi Thakur; K.K. Sahare; A.M. Lakra; Deepak Singh; C.P. Bhagat (International Journal of Medical Research and Review, 2018)
Objective(s): To compare the intubating conditions, onset and duration of action, side effects and complications with rocuronium bromide and atracurium besylate.Material and Method: This prospective, randomized double blind study was conducted with a sample size of 100 patients. After standard general anaesthesia technique group I received IV. rocuronium bromide 0.6 mg/kg and group II received iv. atracurium besylate 0.5 mg/kg. Laryngoscopy was attempted60 sec after administration of NMBA and thereafter every 30 sec till good or excellent intubating conditions were achieved. Intubating condition was scored on fourpoint scale (0-3). Intubating conditions, onset and duration, side effects and complications were observed and recorded.Result: Overall intubating condition was acceptable (excellent + good) in 50(100%) patients in group I and 47(94%) patients in group II. It was excellent in 45(90%) and 16(32%) patients in group I and II respectively. Good intubating condition was found in 5(10%) and 31(62%) patients in group I and II respectively. Fair intubating condition was found in 3(6%) patients in group II. None of the patients had poor intubating condition in either group. Cutaneous flushing was found in 4% cases in group II. No other side effects and complications were observed.Conclusion: Rocuronium with its faster initial response and possibly early laryngeal muscle paralysis provides better intubating conditions in shorter duration of time than atracurium.